IMPLEMENTASI PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS DI SMP NEGERI KABUPATEN PADANG PARIAMAN - Rahman, Aida Fitri; Atmazaki, Atmazaki,; Abdurahman, Abdurahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ The purpose of this study is to describe (1) implementation of the Indonesia-based language learning texts on SMP Negeri Padang Pariaman in the implementation of text-based learning through the four stages of learning, i.e. the stage of preparation of the context the modeling stage, stage, build the text together, and the stage of establishing the text independently, (2) constraints faced by teachers of language subjects in junior high Country Indonesia Padang Pariaman in the implementation of text-based learning. This type of research is qualitative research with a descriptive method. This research was conducted in the State JUNIOR HIGH SCHOOL Padang Pariaman i.e. SMP 1 228 1 lime, Rivers 2X11 Wood Planting, and SMP 1 2X11 Six Group. The data in this study is the result of data collection on the implementation of text-based language learning Indonesia conducted Indonesia language teacher in junior high Country Padang Pariaman are retrieved from the data source. Techniques employed i.e., observation and interview. A technique used to analyze the data, namely the identification data, data presentation, and the withdrawal of the conclusionÂ Kata kunci: Implementation of text-based learning, language learning IndonesiaÂ